The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1183/09031936.00051106
|View full text |Cite
|
Sign up to set email alerts
|

Spacer inhalation technique and deposition of extrafine aerosol in asthmatic children

Abstract: The aim of the present study was to measure airway, oropharyngeal and gastrointestinal deposition of 99m Tc-labelled hydrofluoroalkane-beclomethasone dipropionate after inhalation via a pressurised metered-dose inhaler and spacer (Aerochamber Plus TM ) in asthmatic children.A group of 24 children (aged 5-17 yrs) with mild asthma inhaled the labelled drug. A total of 12 children took five tidal breaths after each actuation (tidal group). The other 12 children used a slow maximal inhalation followed by a 5-10-s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
1
54
1
1
Order By: Relevance
“…Typically lung deposition from the same pMDIspacer combination could be 1-2% in infants, 4-6% in children aged 2-6 years and 12% in a 10-year old child. [17][18][19][20][21] This is also one of the reasons why young children often need almost the same inhaled dose as older children to obtain the desired clinical effect.…”
Section: Aerosol Deposition Patterns In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically lung deposition from the same pMDIspacer combination could be 1-2% in infants, 4-6% in children aged 2-6 years and 12% in a 10-year old child. [17][18][19][20][21] This is also one of the reasons why young children often need almost the same inhaled dose as older children to obtain the desired clinical effect.…”
Section: Aerosol Deposition Patterns In Childrenmentioning
confidence: 99%
“…However, one study found that, when inhaling an extra fine particle formulation from a spacer, one deep inhalation followed by breath-holding resulted in significantly improved lung deposition compared with tidal breathing across all ages in children aged 4 -15 years. 18 In young children the parents should ensure that the valve is moving correctly. 32,36 Crying during the administration or air leakage between the face mask and the face due to a loosely fitting face mask markedly reduces the aerosol delivery to the intra-pulmonary airways (Table 1).…”
Section: Pmdi-spacer Combinationsmentioning
confidence: 99%
“…When compared to the improper use of a pMDI alone, inhalation of the dose through a pMDI connected to a spacer device significantly improved the aerosol lung deposition [1], [13], [14], and reduced both the oropharyngeal [15] and systemic [16] inhaled corticosteroid-related adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the PK study with spacer, after an overnight fasting of at least 10 h, subjects self-administered a single dose of either test or reference product (salmeterol xinafoate HFA 25 μg/actuation × 4 puffs) with the help of a Volumatic spacer. Deep breathing technique was used for inhalation through the spacer device as it has a lesser variability as compared to tidal breathing method [27].…”
Section: Study Productsmentioning
confidence: 99%